Preparing for the impacts of climate change along Canada's Arctic coast: The importance of search and rescue. (October 2019) - Ford, J.; Clark, D.
Abstract: The Arctic is undergoing transformative climate change, with profound implications for transportation safety in marine areas. Circumpolar marine risks are growing due to ship traffic increases linked to more ice-free open water, as well as increases in hazards for individuals that frequently travel on ice and trails in the region. While recent Government of Canada policies have attempted to respond to the growing risk of marine and coastal emergencies, there is strong evidence that the federal government and communities along Canada's Arctic coast are minimally prepared for the emerging risks. In this Short Communication, we argue that Canada is falling short of its international and national obligations to provide timely search and rescue across the Arctic, to the detriment of Arctic communities. Drawing from recently published reports and literature, we argue that providing additional training, resources, and support for volunteer SAR groups across the region is critical, along with increasing federal air and marine resources committed to the region. Such investments need underpin Canada's approach to climate change adaptation in the North.